Victims' Discourses: Filipina Domestic Workers in Germany - Kirk, Maria Carmen Domingo (Review of Women's Studies; Vol 13 No 1 (2003): Review of Women's Studies Volum XIII, Number 1 (January-June 2003), 2003)
---